FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SAFETY DRIVING PADA SUPIR TRAVEL DI PT. LIBRA WISATA TRANSPORT - Ade Dita Puteri; azimah Mardiatun Nisa (Universitas Pahlawan, 2020)
Safety Driving is the basis for further driving training that pays attention to the safety of drivers and passengers. Safety Driving is influenced by human factors such as age, education, length of work, knowledge, vehicle factors such as passenger load capacity, environmental factors in this condition of road and weather. The purpose of this study is to know the factors relating to correlation safety driving of travel driver at PT. Libra Wisata Transport Pekanbaru year 2019. This research is a quantitative study of analytics with a cross-sectional approach. This research was conducted on June 20-25, 2019 with the population in this research is the travel driver of PT. Libra Wisata Transport Pekanbaru, which was 40 people using the Total Sampling technique. independent variables are age, employment, education, length of work, knowledge, and driving completeness, while the dependent variables are the behavior of Safety Driving. The instruments used in data collection are questionnaires. Data analysis is conducted with the analysis of univariate and bivariate with Chi-Square test. The results of the research can be a relationship between age, employment, education, duration of work, knowledge and completeness of driving with the behavior of Safety Driving. It is suggested to the travel to be able to conduct training on Safety Driving to the all of driver, and conduct evaluation on the implementation of Safety Driving training, so that the results of the training can make the driver Act securely In driving. In addition, the driver is expected to always obey the ordinances of the traffic provisions.